Age Related Cognitive Function Was Positively Associated with Diastolic Pressure and Negatively Associated with Antibody Expression in Chinese Oldest-Old and Centenarian Adults - Feng L; Wu D; Ping P; Lin J; Zhao Y; Yao Y; Zhang P; Fu S (Dove Medical Press, 2022)
Long Feng,1,* Di Wu,2,* Ping Ping,3,* Jieqiong Lin,4,* Yali Zhao,5 Yao Yao,6,7 Pei Zhang,8 Shihui Fu2,9 1Department of Anesthesiology, Hainan Hospital of Chinese People's Liberation Army General Hospital, Sanya, People's Republic of China; 2Department of Cardiology, Hainan Hospital of Chinese People's Liberation Army General Hospital, Sanya, People's Republic of China; 3General Station for Drug and Instrument Supervision and Control, Joint Logistic Support Force of Chinese People's Liberation Army, Beijing, People's Republic of China; 4Department of Pathology, Fujian Medical University Cancer Hospital, Fujian Cancer Hospital, Fuzhou, People's Republic of China; 5Central Laboratory, Hainan Hospital of Chinese People's Liberation Army General Hospital, Sanya, People's Republic of China; 6Center for the Study of Aging and Human Development and Geriatrics Division, Medical School of Duke University, Durham, NC, USA; 7Center for Healthy Aging and Development Studies, National School of Development, Peking University, Beijing, People's Republic of China; 8School of Life Science, Beijing Institute of Technology, Beijing, People's Republic of China; 9Department of Geriatric Cardiology, Chinese People's Liberation Army General Hospital, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Shihui Fu, Department of Cardiology, Hainan Hospital of Chinese People's Liberation Army General Hospital, Sanya, People's Republic of China, Email xiaoxiao0915@126.com Yali Zhao, Central Laboratory, Hainan Hospital of Chinese People's Liberation Army General Hospital, Sanya, People's Republic of China, Email zhaoyl301@163.comPurpose: Age related cognitive function (ARCF) is of increasing concern in an aging population. Few studies have examined the relationships between ARCF and antibody expression or blood pressure, particularly in older populations. Large sample sizes are needed to elucidate these relationships to inform better strategies for identification and prevention of cognitive decline. The present study was designed to investigate these relationships in Chinese oldest-old and centenarian adults.Patients and Methods: A household survey was performed that included 436 centenarians and 520 oldest-old adults (80- 99 years) residing in 16 cities and counties of Hainan province, China. ARCF was assessed using the mini-mental state examination.Results: The median age of participants in this study was 92 years, with a range of 80 to 116 years. Females accounted for 68.5% (655) of the participant pool. Multivariate linear regression analysis showed that age [Exp(B): − 0.220, 95% confidence interval (CI): − 0.270--0.169], female gender [Exp(B): − 3.459, 95% CI:-4.458--2.460], Han ethnicity [Exp(B): − 1.732, 95% CI: − 2.693--0.772], serum creatinine [Exp(B): − 0.019, 95% CI: − 0.037--0.001], immunoglobulin light chain KAP [Exp(B): − 0.008, 95% CI: − 0.015- 0.000], and anti-ribonucleoprotein antibody [Exp(B): − 6.393, 95% CI: − 10.898--1.887] were negatively associated with ARCF (P < 0.05). Coronary artery disease [Exp(B): 1.957, 95% CI: 0.170- 3.744] and diastolic pressure [Exp(B): 0.041, 95% CI: 0.002- 0.079] were positively associated with ARCF (P < 0.05).Conclusion: ARCF was positively associated with diastolic pressure and negatively associated with antibody expression in Chinese oldest-old and centenarian adults.Keywords: age related cognitive function, antibody expression, centenarian, diastolic pressure, oldest-old